2018
DOI: 10.1177/0300060518765344
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of the oblique-axis plane in ultrasound-guided internal jugular vein puncture: A meta-analysis

Abstract: ObjectiveThis meta-analysis was performed to evaluate the safety and efficacy of the oblique-axis plane in ultrasound-guided internal jugular vein puncture.MethodsWe searched Embase, PubMed, the Cochrane Library, Web of Science, and China National Knowledge Infrastructure for relevant randomized clinical trials comparing the oblique axis with the short axis in ultrasound-guided internal jugular vein puncture.ResultsFive randomized clinical trials were included in this meta-analysis. The pooled meta-analysis sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
4
0
2
Order By: Relevance
“…Different studies have detailed approaches to ultrasound‐guided IJV cannulation, each with their own advantages and disadvantages 15 . Some meta‐analyses show insufficient evidence to confidently recommend the LA, SA or OA approaches for patients undergoing ultrasound‐guided vascular access cannulation 16‐19 . However, a growing number of scholars advocate for the OA‐IP technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have detailed approaches to ultrasound‐guided IJV cannulation, each with their own advantages and disadvantages 15 . Some meta‐analyses show insufficient evidence to confidently recommend the LA, SA or OA approaches for patients undergoing ultrasound‐guided vascular access cannulation 16‐19 . However, a growing number of scholars advocate for the OA‐IP technique.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that real-time ultrasound-guided techniques can significantly reduce the number of attempts to cannulate and achieve a higher first-needle-pass success rate, quicker cannulation time, and exhibit fewer complications in IJV cannulation. [16][17][18][19] However, a growing number of scholars advocate for the OA-IP technique. For example, Baidya et al 20 showed that the medi- Abbreviations: IJV, internal jugular vein; N, number; SD, standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…16 Similar was seen by the studies done by Chuan et al and Batlori et al where this success was seen in 100% and 96.4% of the cases where the latter used the oblique technique and the first attempt success rate was highest. 7,18 In a meta-analysis regarding the success rate and complications of the oblique-axis plane, it was demonstrated that ultrasound guided IJV cannulation with oblique-axis plane may also reduce the chances of carotid artery puncture. 18 The in-line oblique-axis technique provide the advantages of the both SAX and LA approaches in one ultrasound guided view.…”
mentioning
confidence: 99%
“…7,18 In a meta-analysis regarding the success rate and complications of the oblique-axis plane, it was demonstrated that ultrasound guided IJV cannulation with oblique-axis plane may also reduce the chances of carotid artery puncture. 18 The in-line oblique-axis technique provide the advantages of the both SAX and LA approaches in one ultrasound guided view. Once mastered, it is likely that with inline oblique axis probe position allowing for visualization of both the carotid artery and IJV while observing the needle advancement into the vein would minimize the risk of many complications associated with CVC insertions.…”
mentioning
confidence: 99%
“…Ha mostrado muy buenos resultados en la canalización de la yugular interna en adultos, aunque existe menos experiencia en niños. (76,83) Figura 1.31 (31): Abordajes ecoguiados alternativos. Inserción de la aguja en transversal en plano (a).…”
Section: Relación Plano-vaso-aguja: Abordajeunclassified